The impact of interest rate spread on the banking system efficiency in South Africa - Varaidzo Batsirai Shayanewako; Asrat Tsegaye (Cogent Economics & Finance, 2018)
The banking industry is the engine of economic activities of the modern day financial systems. As such, banks play a very significant part in supporting economic growth through the efficient allocation of resources and risk diversification in an environment of optimal interest rate spread. Therefore, the understanding of the impact of interest rate spread on the banking system efficiency demands that an empirical inquiry of this nature be conducted. In this paper, we seek to empirically investigate the impact of interest rate spread on the banking system efficiency in South Africa for the period from 2000Q1 to 2017Q3 by employing the nonlinear autoregressive distributed lags framework. Evidence from this study suggests the presence of asymmetries in the interest rate spread behavior. Specifically, in the long run, we find a significant negative relationship between banking efficiency and a positive shock to interest rate spread. Furthermore, a negative shock to interest rate spread improves banking efficiency by about 0.3% in the long run. The results of this study further suggest that economic growth and real exchange rate are significant factors that positively influence the banking system efficiency and nonperforming loans retard the efficiency of the banking system in South Africa.
Keywords: 330; risk diversification; interest rate spread; banking system efficiency; nonlinear autoregressive distributed lags